Emergency planning for nuclear power plants - Elkmann, Paul (CRC Press, 2021)
This book provides a history of emergency planning with respect to nuclear power plant accidents from the 1950's to the 2000's. It gives an overview of essential concepts that a working emergency planner should know, including brief overviews of the health physics and plant engineering that applies to emergency planning. Each chapter covers topics unique to radiological planning that distinguish it from planning for natural disasters. Some of the topics include processes that damage fuel, reactor source terms, basic dispersion theory, protective measures for the public and emergency worker, environmental surveys, and the essential elements of a drill and exercise program. Emergency Planning for Nuclear Power Plants is not intended as a guide to meeting regulatory requirements but provides an understanding of the essential concepts and language of radiological planning, so the planner can apply those concepts to their particular situation.